Civilization: from Hypotheses, Legends and Epics to Legal Certainty - Zhukov, Vasily I. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
The author considers various tales, epics and hypotheses reflecting the ideas of different peoples about the concept of civilization, establishes historical and legal differences between formational and civilizational concepts, and provides ideas about the degree of reality of certain hypotheses. The author in their work has analyzed the reliability of contemporary information characterizing the features of ancient and modern versions of certain civilizations, in connection with the time of their appearance, features of their genesis, and the specific lower and upper frames of their existence. The author highlights the mental features of the Russian civilization, which made a significant contribution to the progress of mankind. The author comes to the conclusion that civilization has several stages of its development and Russia occupies a special place in the system of world civilizations, since it is a state within whose borders there were in turn many civilizations, a existence representing unity in diversity through common borders, a common state language, a joint system of governance with domestic and foreign policy at the prerogative of the state. The national character is expressed in the language, as well as customs, morals, culture, way of life, administrative borders, etc.